Toward Label-Free Biosensing With Silicon Carbide: A Review - Oren Cooper; Bei Wang; Christopher L. Brown; Joe Tiralongo; Francesca Iacopi (IEEE Access, 2016)
Recent innovation in microelectrical-mechanical systems (MEMSs) and plasmonics-based technologies has opened up perspectives for label-free sensing of biological and chemical analytes. Label-free sensing would enable increased sensitivity and miniaturization capabilities for biosensing devices. Silicon carbide is a semiconductor material that happens to possess ideal properties for augmenting both the MEMS/nanoelectromechanical systems and the plasmonics routes. It has remarkable chemical and biological inertness resulting in a high degree of biocompatibility, as well as pronounced mechanical resilience. In addition, it is an efficient (low loss) plasmonic metamaterial. Its cubic polytype can be grown on silicon wafers, allowing easy micromachining into building blocks for sensing devices, scalable to large volume production. Finally, silicon carbide is an ideal starting material for a controlled, wafer-scale growth of graphene, offering an additional wealth of excellent properties for nanosensing. The combination of all of these capabilities makes silicon carbide an outstanding material platform for the realization of label-free, analyte-specific, and highly sensitive biochemical molecule detection systems. These technologies will open exciting horizons in terms of high throughput, efficient drug screening, and early pathogen detection.